Housing as an instrument for violence manifestations of violence in Taljomulco de Zúñiga, México - Lau Velázquez, Jessica (Premio Internacional de tesis 2021. Vivienda y barrios abandonados: hacia una regeneración urbana integral, 2019)
This thesis will examine how the national housing policies from 2000-2018 in Mexico have been instrumental in propagating structural, economic and physical violence in the country through the lack of urban planning and the inadvertent transfer of power to non-state actors - arguing that economic and structural factors have instrumentalised physical violence through the failures of these national housing policies. The complex relation between housing policies and the manifestation of structural and physical violence will be conceptualised in a framework that positions the relationship between the failures of the policy and the escalating manifestations of violence through a period of 18 years. This will first be read on a national scale using Arendt's theory of the relation between power and violence, in which Arendt (1970) claims